2018
DOI: 10.1038/s41598-018-23870-w
|View full text |Cite
|
Sign up to set email alerts
|

Dysbiosis of the salivary microbiota in pediatric-onset primary sclerosing cholangitis and its potential as a biomarker

Abstract: Primary sclerosing cholangitis (PSC) is a liver disease known for its frequent concurrence with inflammatory bowel disease. Dysbiosis of the gut microbiota in PSC was reported in several studies, but the microbiological features of the salivary microbiota in PSC have not been established. Here we compared the salivary microbial communities of 24 pediatric-onset PSC patients, 16 age-matched ulcerative colitis (UC) patients, and 24 healthy controls (HCs) by analyzing the bacterial 16S rRNA gene sequence data. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(46 citation statements)
references
References 50 publications
1
45
0
Order By: Relevance
“…More recently, the first data on the salivary microbiome in patients with PSC was reported, based on a cohort of newly diagnosed, paediatric PSC patients from Japan, where faecal microbiota composition was in line with the description above . The salivary microbiome was characterized by changes in bacterial taxa that mirror the findings from faecal microbiota, with Haemophilus spp , Veillonella spp and Streptococcus spp being different between paediatric PSC patients and age‐matched controls.…”
Section: Introductionmentioning
confidence: 53%
“…More recently, the first data on the salivary microbiome in patients with PSC was reported, based on a cohort of newly diagnosed, paediatric PSC patients from Japan, where faecal microbiota composition was in line with the description above . The salivary microbiome was characterized by changes in bacterial taxa that mirror the findings from faecal microbiota, with Haemophilus spp , Veillonella spp and Streptococcus spp being different between paediatric PSC patients and age‐matched controls.…”
Section: Introductionmentioning
confidence: 53%
“…Provided that our results are confirmed by others, one can envision using faecal microbiota-based biomarkers as a diagnostic tool in patients with suspected PSC. This type of strategy has already been proposed,13 16 18 notably by Iwasawa et al who recently reported a characteristic dysbiosis of the salivary microbiota in children with PSC 47. Furthermore, specific alterations of the gut microbiota found in PSC could be used to design new therapeutic strategies, as recently proposed for alcoholic liver disease 48…”
Section: Discussionmentioning
confidence: 96%
“…No relation between Oribacterium and NAFLD has been described to date. Nonetheless, this genus could be related to liver disease as increased relative abundance of Oribacterium has been found in salivary microbiota of primary sclerosing cholangitis patients . On the contrary, Oscillospira has been related to a healthy metabolic profile, being diminished in obese adults and pediatric NAFLD patients …”
Section: Discussionmentioning
confidence: 99%